The Effectiveness of Surgeon Decision on Pain Syndrome of Pelvic Origin Treatment in Women Estimated with the Model of Decision Tree - Buzynovsky, А.B.; Kоvalenko, О.S.; Bayazitov, N.R.; Godlevsky, L.S. (Кибернетика и вычислительная техника, 2018)
The purpose of the work is to investigate the effectiveness of different methods of treatment women with pain syndrome originated from pelvis and lower part of abdomen on the basis of retrospective analysis of 1092 histories of diseases during 2013–2017 р.р., Results. It was established that the probability of complete health restoration was 0,83 after surgical treatment and 0,62 after drug treatment. In case of initial inefficiency of drug treatment the probability of restoration of health as a result of surgical intervention was 0,40. The EPT in surgically treated patients was less than EPT in patients with therapeutic treatment by 3,29 times at the moment of making decision on the method of treatment.